Sob as sombras da guerra : cinema Noir, história e masculinidades - Araujo, Tatiana Brandão de (2020)
The American film noir and the discussions about masculinities comprise the object of this doctoral dissertation. Even though this movement marked the 1940s and the 1950s, the main focus of the research consists on the years after the end of the Second World War, and how some discourses about the comeback of the veterans and their readjustment to civil life were presented in a variety of ways in those films. Its guiding question is the search for better understanding of the representation of male characters in film noir and their inter-relations with national narratives, such as the relation between Hollywood cinema with current discourses since the revolutionary process. Therefore, it highlights the ideals presented on the Declaration of Independence and in the conquest of the West in the 19th century, as an influence on mass culture in the 20th century and in the way the films intertwine with issues related to the “American Dream”, and what they reverberate about notions on nation, family and gender. The research is directed to the past for a better understanding of some ideals in the American culture, while updating questions that are still present in current productions. Thus, this dissertation aims at establishing dialogues among film noir, the years after Second World War in the United States and its national narratives. The specific objectives are: to emphasize the importance of the discussions about fictional objects to History; to present discussions about film aesthetics as a central aspect for the understanding of its themes; and to discuss noir in its cinematic context and in what way these films also construct a dialogue with productions of the same period. The study is mainly structured through discussions by Judith Butler (2003), bell hooks (2004) and R.W.Connell (2015) about gender and masculinities; by Frank Krutnik (1991) and Richard Dyer (2002/1998) about masculinities and film noir; and by Ray Raphael (2006) for the debate about the structures of the American past as mythical narratives. Regarding methodology, this qualitative research applies the formal and thematic analysis of the films in the context under investigation. A table with all the films noir that were watched during the research period was built; it enabled to verify common elements of these productions which characterize the period under study. Final remarks show indelible marks that certain values have in the American culture, as well as the importance of film noir to the cinema of the period and what came later.